Simulation-aided production of aircraft's composite parts - Mohd Nawawi, Mohd Kamal; Tahar, R. M.; Omar, Zurni (Universiti Utara Malaysia, 2004)
Simulation has been successfully applied in many different areas such as manufacturing, service system, healthcare, transportation, supply chain, and etc. The opportunities to cut costs and to improve service levels in these sectors are tremendous by applying this technology. One of the largest application areas for simulation modelling is that of manufacturing systems, which has been applied for more than 40 years. This study is conducted at the local manufacturing plant that manufactures composite products for the aerospace industry. In this study, simulation technique is applied to model the existing system to simulate the design and operational policies of the plant production process, which can be used to improve the performance of the different activities at the plant. The model focused on activities at Secondary Manufacturing Area (SMA) of aircrafts composites parts.